Método fuzzy para la identificación de áreas potenciales para la producción de leña. Aplicación de caso: comuna de Empedrado, región de Maule, Chile - Garfias Salinas, Roberto; Castillo Soto, Miguel; Yánez Leiva, Adolfo (Geographicalia, 2014)
Potential areas for establishing wood energy plantations in the Empedrado municipality, Maule region, were identified using environmental and territorial criteria. For this purpose, five forest species were proposed, Acacia dealbata, Acacia melanoxylon, Chamaecytisus proliferusssp. palmensis, Eucalyptus camaldulensis and Robinia pseudoacacia. Suitability land models for wood energy plantations for each propose species were elaborated, in order to quantify and locate areas of high, medium and low suitability. The suitability of the land was evaluated integrating the opinion of experts in forest plantations and wood energy add cartographic and digital information available of the Empedrado municipality, besides the environmental requirements of the species. Nine environmental variables were hierarchized, spatially represented and transformed into a common scale by using Geographic Information Sistem (GIS). When comparing these models the Chamaecytisus proliferus is the species with the highest suitability in 70.3% of the surface available, whereas Robinia pseudoacacia appears as not recommendable.
Keywords: Maule; Chile; fuelwood production; Fuzzy Logic; GIS.